KOMPENSASI PRODUKSI CO2 DARI PEMBANGUNAN INFRASTRUKTUR DENGAN SERAPAN CO2 OLEH VEGETASI - Syaukat Ali (Geo Media: Majalah Ilmiah dan Informasi Kegeografian, 2012)
The global warming issue, with increasing CO2 concentration level, has become  agloba lproblem. The increasing of the CO2 is caused by the high emission of CO2 produced by several sectors, mainly from road and building infrastructure sectors. Buildings are responsible for CO2 production from their use of electricity, while road infrastructure, by means of the transportation system, plays a role in the CO2 hike. It is by no means arare occasion that trees alongside roads and streets are being cut down since they are believed to take much of the landused for transpotation. Whereas, as we all see, trees and vegetation are able to absorb and limit CO2 emission. Thus, the tree-cutting activities and the increase of CO2 emission constitute environmental cost which mustbe “paid” by regularly planting trees. By doing so, environmental balance is attained as trees readily absorb CO2 emission from both road and building infrastructures.The aim of this research is to develop a formula to calculate the environmental cost, thus named “CO2 compensation system,” by both measuring CO2 production cost from community’ senergy consumption and analyzing a survey on transportation energy consumption. Field observations are conducted to know the CO2 production character in the sample site. The data collected are therefore analyzed quantitatively using a computer program to attainan exact CO2 compensation formula.The result of the study reveals that community’s (families) domestic energy/electricity consumption in directly produces emission of 679.46kgs of CO2 permonth. To compensate that, vegetation which can absorb the amount of 679.46kgs of CO2 per month is decidedly needed. In addition,from the transportation sector, each motor vehicle reaches anaverage of 539.43kms/monthonroad. Its CO2 emission produced permonth is 62.22kgs/vehicle in average.Kata Kunci: CO2, pembangunan infrastruktur, vegetasi